Enhancer Prediction in Proboscis Monkey Genome : A Comparative Study - Norshafarina, Omar; Lee, Nung Kion; Yu, Shiong Wong; Xi, Li; Chong, Yee Ling; Mohd Tajuddin, Abdullah (2017)
Genome annotation is an essential task for understanding and analyzing the whole genome and its function. We have sequenced the complete proboscis Monkey (Nasalis larvatus) genome due to its important for medical and evolutionary studies. We have performed an initial annotation of the genes genome using the MAKER gene annotation pipeline. 3084 genes were predicted from chromosome 18 of the genome using six eukaryotic model species. Intergenic regions possibly enriched with enhancers are then predicted using five different tools: DeepBind, LS-GKM, GMFR-CNN, CSI-ANN and iEnhancer-2L. These tools find the enhancers of the complex intergenic regions based on epigenetic features, in which intergenic regions are seen as a potential region for enhancers with a certain epigenetic features bound to it. Empirical results demonstrate competitive performance using different prediction tools with multiple epigenetic features to predict the enhancers for chromosome 18 in proboscis monkey. Based on the finding of this study, predicted enhancers can be used for the purpose of scientific and genomic discoveries.